The Optimal Exploitation of an Unknown Reserve - Loury, G. C. (Review of Economic Studies, 1978)
Journal Article The Optimal Exploitation of an Unknown Reserve Get access Glenn C. Loury Glenn C. Loury Northwestern University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 3, October 1978, Pages 621–636, https://doi.org/10.2307/2297264 Published: 01 October 1978 Article history Received: 01 November 1976 Accepted: 01 October 1977 Published: 01 October 1978